Food Is Medicine: Providing Medically Tailored Meals to Community Members with Disease-associated Nutritional Risk Supports Stable BMI and Decreased Hospitalization (P12-005-19). (13th June 2019) - Henstenburg, Jule Anne; Parvanta, Claudia; Pontiggia, Laura; Daugherty, Sue; Laverty, Nicole
Abstract: Objectives: MANNA, a Food is Medicine organization in Philadelphia, provides nutritional support for community members at nutritional risk from serious illness. MANNA's program of medically-tailored meals and nutrition counseling have been associated with lower healthcare utilization and costs, however the specific health outcomes that contribute to these effects are unknown. The objective of this research is to analyze change in body mass index (BMI) and proportion of recent hospitalizations in association with MANNA's program. Methods: A retrospective chart review was conducted for 103 clients who answered a 2016 Client Satisfaction Survey and received at least six months of MANNA's program between Jan. 2015 and Dec. 2016. Data from the start of services and at 6-months follow-up were entered into Research Electronic Database Capture (REDCap) and analyzed using Statistical Analysis Software (SAS). Results: The median age of clients in the sample was 66.0 years (interquartile range (IQR) 58.0—72.0). Primary diagnoses were cancer (53%), renal disease (15.7%), diabetes (7.8%), HIV/AIDS (3.9%), heart disease (3.9%) and "other" (16.7%). Half of the sample (52.0%) reported having insufficient money to buy food. Per weight history, two-thirds (63.3%) of clients had decreasing weight before program enrollment, 28.9% had stable weight and 7.8% had increasing weight. Change in BMI between initial intake and recertification was: median = 0.04; IQR (−0.84, −1.02). Analysis of variance followed by a multiple comparisons with a Bonferroni adjustment found no evidence of any difference in BMI change between diagnoses. Bivariate analysis with t-tests found no evidence of any difference in BMI change between clients with enough money for food and those without ( P = 0.4277). McNemar's Test found evidence of a significant decrease in the proportion of clients who had recent hospitalizations at follow-up compared to the start of services ( P = 0.0077). Conclusions: Manna's program was associated with stable BMI. Change in BMI was not significantly different based on primary diagnosis or insufficient money to buy food. The proportion of client hospitalizations was significantly less after MANNA's program. Stabilization of BMI is a possible health outcome that contributes to lower healthcare utilization and cost savings in MANNA's clients. Funding Sources: None.